2007
DOI: 10.1097/cji.0b013e31802e085a
|View full text |Cite
|
Sign up to set email alerts
|

The New B7s: Playing a Pivotal Role in Tumor Immunity

Abstract: B7-H1, B7-DC, B7-H2, B7-H3, and B7-H4, all new additions to the B7 family, here termed "the new B7s," are emerging as important tools in directing immune function; each with unique, yet often overlapping functions. Clearly, each B7 molecule has developed its own indispensable niche in the immune system. The expression of both stimulatory and inhibitory B7 molecules seems to play an essential role in regulating the immune response to transformed cells through a variety of mechanisms. As specific niches of B7 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
136
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 118 publications
3
136
0
Order By: Relevance
“…The costimulatory B7 family members are cell-surface protein ligands, binding to receptors on lymphocytes to regulate immune responses (Flies et al, 2007). They not only provide positive signals to stimulate T-cell activation, but also regulate negative signals to inhibit T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The costimulatory B7 family members are cell-surface protein ligands, binding to receptors on lymphocytes to regulate immune responses (Flies et al, 2007). They not only provide positive signals to stimulate T-cell activation, but also regulate negative signals to inhibit T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the activation of the B7-H4 signaling pathway may lead to tumor cells escaping from immune surveillance (Flies and Chen, 2007;Arigami et al, 2011;Sun et al, 2012). Recent report showed that host B7-H4 may enable metastasizing cancer cells to escape local antitumor immune responses through interactions with the innate and adaptive immune systems (Abadi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…12 PD-1 expression has also been identified on a small fraction of melanoma cells, where its ligation promotes tumor growth. 13 The known ligands for PD-1 are the B7 family molecules PD-L1 (B7-H1, CD274) and PD-L2 (B7-DC, CD273), [14][15][16][17][18][19][20] which are cell membrane-bound glycoproteins that share 40% amino acid homology to each other. In normal human tissues, PD-L1 is expressed by myeloid dendritic cells (DC), macrophages, placental trophoblasts, myocardial endothelium and cortical thymic epithelial cells, 21,22 whereas PD-L2 is expressed by DC, macrophages, placental endothelium and medullary thymic epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas HLA-B-associated transcript 3 has been reported to be expressed by both malignant and healthy cells such as dendritic cells (16,18), B7-H6 to date has not been found on normal cells, suggesting that this ligand may be exclusively displayed by aberrant cells and to be absent from healthy tissues (15,21). The ligand B7-H6 belongs to the B7 molecule family comprising several members that exert both immune stimulatory and inhibitory functions (22). The tumor-restricted expression pattern, binding specificity for the stimulatory NKp30 receptor, and its ability to trigger NK cell cytotoxicity suggest that B7-H6 may play a pivotal role as an "induced self" alert signal for NK cells.…”
mentioning
confidence: 99%